Legal Protection for Land Rights Owners on Cancellation of Certificates by the Court Due to Overlapping - Agree Deardo Simarmata; Tetti Samosir; Jum Anggriani (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
This research examines the overlapping land ownership dispute between Certificate of Land Ownership (SHM) No. 39/Desa Pulau Sari of 1978, owned by the heirs of Rusdiansyah Bin Haji Sabri Razak, and SHM No. 748/Desa Bingkulu of 2010, owned by Sundariati, based on Decision No. 11/G/2021/PTUN.Bjm. The main issue discussed is the annulment of SHM No. 748 by the State Administrative Court of Banjarmasin and the legal protection available to the certificate holder whose certificate was annulled. This study uses a normative approach with qualitative analysis of secondary data, including laws, jurisprudence, and related literature. The main finding of this research shows that discrepancies in the land registration system, the transition to digital measurement, and administrative weaknesses led to overlapping land certificates. In this case, although the annulment of the certificate by the court provides legal certainty for the previous right holder, the holder of the annulled certificate, Sundariati, may seek protection through a tort claim based on Article 1365 of the Indonesian Civil Code. This research emphasizes the need for reforms in the land registration system to enhance protection for bona fide right holders and prevent future disputes.